Pelvic floor shape variations during pregnancy and after vaginal delivery. (October 2020) - Routzong, Megan R.; Rostaminia, Ghazaleh; Moalli, Pamela A.; Abramowitch, Steven D.
Highlights: The pelvic floor shapes of nulliparous, gravid, and parous women were compared. Statistical shape modeling quantified midsagittal pelvic floor shape variation. Only the nulliparous and gravid groups differed significantly for each significant mode. 3rd trimester gravid levator plates were more vertical than in nulliparous controls. These results demonstrate lasting shape changes after pregnancy and vaginal delivery. Abstract: Background and objective: Strong evidence suggests that pelvic soft tissues soften during pregnancy to facilitate vaginal delivery while protecting against maternal birth injury. We hypothesized that these adaptations likely result in changes to the shape of the pelvic floor. Thus, this study aimed to compare midsagittal pelvic floor shapes from MRIs of nulliparous, gravid, and vaginally parous women using statistical shape modeling. Methods: A retrospective study of 22 nulliparous, 29 gravid (vaginally nulliparous), and 18 vaginally parous women who underwent pelvic MRI was performed. The pelvic floor was segmented from pubic symphysis to coccyx as a 2D polyline in the midsagittal plane. Once corresponding landmarks were computed and the variances between them determined by principal component analysis, the principal component scores were calculated for modes that explained variance greater than noise. These became the dependent variables in a MANOVA with univariate ANOVAs, linear regressions, and Benjamini-Hochberg corrections post hoc. Two initial statistical shape analyses were conducted to analyze differences based on gestational age (1 st /2 nd vs 3 rd trimester) and vaginal parity (VP1 vs VP2-4). There were significant differences based on gestational age, but not vaginal parity. Thus, the final statistical shape analysis evaluated pelvic floor shapes of nulliparous, 3rd trimester gravid, and all vaginally parous subjects. Results: In the final analysis, six modes described variance—a measure of shape variability—greater than noise. Groups differed significantly for modes 1, 2, and 4 ( p  < 0.001, p  = 0.021, and p  = 0.015, respectively) and only differed between the nulliparous and gravid groups ( p  < 0.001, p  = 0.018, and p  = 0.012, respectively). Anatomically, these modes described levator plate relaxation and level III support protrusion in gravid compared to nulliparous subjects while the parous group straddled the other two. Conclusions: The shape of the pelvic floor changes significantly during pregnancy and some of those changes are present after vaginal delivery. The fact that the nulliparous and gravid groups differ while the parous is similar to both suggests that some parous women regain their nulliparous shape after pregnancy and delivery while others do not. This indicates that remodeling during pregnancy and/or injury during vaginal delivery can have lasting effects on the pelvic floor.